EFFECT OF DILLENIA INDICA L. AGAINST OXIDATIVE STRESS-INDUCED CARDIOMYOPATHY ON ALLOXAN-INDUCED DIABETES MICE MODEL - Sahariah, Plabita; Bora, Jutishna; Syiem, Donkupar; Bhan, Surya (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of the present study is to investigate the antihyperglycemic and antioxidative properties of Dillenia indica fruits. Methods: Aqueous fruit extract and methanolic fruit extract (MFE) were prepared, and preliminary phytochemical screening was carried out. Diabetic mice were prepared with alloxan (150 mg/kg) body weight (b.w.). Antihyperglycemic study of short duration was carried out with doses (150–550) mg/kg b.w. of MFE in diabetic mice. Antioxidant enzymes (superoxide dismutase, catalase, and glutathione reductase) activity assays and histopathological analysis were done in heart tissue of mice. Results: Preliminary phytochemical screening showed that the phytoconstituents were strongly present in the MFE and therefore was considered for further studies. From the antihyperglycemic study, it was found that 350 mg/kg b.w. dose was the most effective in reduction of blood glucose level. A significant increase in the activities of the antioxidant enzymes was observed in the MFE-treated group. From the histopathological studies, it was observed that detrimental effects of oxidative stress were attenuated in the treated group. Conclusion: Concluding the studies, it could be ascertained that D. indica fruits were found to be quite effective in proving its potential against hyperglycemia and oxidative stress, and therefore, the fruits could be considered to be of therapeutic value in diabetes.